2010
DOI: 10.1152/jn.00077.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Motor Redundancy: Adaptive Increase in Finger Force Variance in Multi-Finger Tasks

Abstract: We studied the effects of fatigue of the index finger on indices of force variability in discrete and rhythmic accurate force production tasks performed by the index finger and by all four fingers pressing in parallel. An increase in the variance of the force produced by the fatigued index finger was expected. We hypothesized that the other fingers would also show increased variance of their forces, which would be accompanied by co-variation among the finger forces resulting in relatively preserved accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 74 publications
9
73
2
Order By: Relevance
“…Some studies have shown that in motor tasks that involve a redundant set of elements, the goal-relevant features of performance are relatively preserved during fatigue (Gates & Dingwell, 2008; Huffenus, Amarantini, & Forestier, 2006). We have also shown this to be true in accurate force production tasks (Park, Singh, Zatsiorsky, & Latash, 2012; Singh et al, 2010b; Singh, Zatsiorsky, & Latash, 2012). In the current study, we investigated the effects of exercise-induced fatigue of a single digit on motor variability and digit coordination in a static prehension task.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some studies have shown that in motor tasks that involve a redundant set of elements, the goal-relevant features of performance are relatively preserved during fatigue (Gates & Dingwell, 2008; Huffenus, Amarantini, & Forestier, 2006). We have also shown this to be true in accurate force production tasks (Park, Singh, Zatsiorsky, & Latash, 2012; Singh et al, 2010b; Singh, Zatsiorsky, & Latash, 2012). In the current study, we investigated the effects of exercise-induced fatigue of a single digit on motor variability and digit coordination in a static prehension task.…”
Section: Introductionsupporting
confidence: 54%
“…Previous studies on exercise induced muscle fatigue have shown an increase in motor variability (Enoka & Stuart, 1992; Singh, SKM, Zatsiorsky, & Latash, 2010b) and altered motor coordination (Côté, Mathieu, Levin, & Feldman, 2002; Forestier & Nougier, 1998; Missenard, Mottet, & Perrey, 2008). Some studies have shown that in motor tasks that involve a redundant set of elements, the goal-relevant features of performance are relatively preserved during fatigue (Gates & Dingwell, 2008; Huffenus, Amarantini, & Forestier, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The basal ganglia have been implicated in action initiation (Sanes 1985;Stelmach et al 1986); in particular, episodes of freezing typical of PD have been interpreted as reflecting the impaired action preparation processes (Vercruysse et al 2011). Our observations of the significantly reduced and delayed ASAs suggest a specific problem with action initiation in PD.…”
Section: Possible Neurophysiological Mechanisms Of Impaired Synergiesmentioning
confidence: 99%
“…Changes in enslaving have been documented over years of specialized practice (Slobounov et al 2002), with healthy aging (Shinohara et al 2003, and with neurological disorder (Park et al 2012). Several recent studies have provided evidence for changes in enslaving occurring relatively quickly, over a single 1-h session involving finger fatigue or specialized practice (Singh et al 2010;Wu et al 2013). The results presented here suggest that enslaving may be an even more volatile phenomenon than the previously cited articles suggest: we observed changes in enslaving within a single trial, over the time course of seconds (Fig.…”
mentioning
confidence: 99%